Amalan Pengurusan Berasaskan Sekolah, Pengupayaan Dan Autonomi Pedagogi Guru Sekolah Rendah - Isa, Anniliza Mohd (2022)
Teacher pedagogical autonomy and empowerment are key elements in school-based management practices. This study aims to identify the level and influence of school-based management practices and empowerment on the pedagogical autonomy of primary school teachers. In addition, this study analyzes the influence of empowerment as a mediator on the relationship between school- based management practices and teachers' pedagogical autonomy. This study used a mixed method approach with a sequential explanatory design that is carried out through two phases, namely the quantitative and qualitative phases. Data collection method consist of survey and interview that are conducted online using google form and google meet. As for the survey method, the questionnaire instrument used to collect data consists of four main parts, namely demographics, teacher pedagogical autonomy, school-based management practices and empowerment. All three instruments have high Cronbach's Alpha values which are APG = .85, APBS = .92 and empowerment = .84. A total of 565 primary school teachers in Sabah were involved as survey respondents who were selected through stratified random sampling. While 8 teachers were involved as interview informants obtained through purposive sampling. The data was then analyzed using IBM SPSS version 25 for the quantitative phase and Atlast.ti version 9 for the qualitative phase